Determinants of alcohol consumption and marijuana use among young adults in the Republic of Palau - Mizuki Sata; Renzhe Cui; Chifa Chiang; Singeru Travis Singeo; Berry Moon Watson; Hiroshi Yatsuya; Kaori Honjo; Takashi Mita; Everlynn Joy Temengil; Sherilynn Madraisau; Kazumasa Yamagishi; Atsuko Aoyama; et al. (Environmental Health and Preventive Medicine, 2021)
Abstract Background This study aimed to describe the status of alcohol consumption and drug use among young adults as well as their determinants. Methods We conducted a cross-sectional study of 356 young adults (aged 18 to 24 years) living in Palau in 2013. The prevalence of self-reported alcohol and marijuana usage were compared within and between sexes, age groups, ethnicities, and education levels. Results The proportion of current drinking was higher in people aged 21–24 than in those aged 18–20 (73.2% vs. 60.9%, p = 0.09 in men and 48.3% vs. 30.0%, p = 0.02 in women), while that of marijuana use did not differ between the age groups. The proportions of current drinking and marijuana use were higher in Palauan than in other ethnicities (current drinking: 70.6% vs. 40.6%, p = 0.005 in men and 38.8% vs. 16.6%, p = 0.04 in women; lifetime marijuana use: 80.0% vs. 52.9%, p = 0.02 in men and 56.1% vs. 30.6%, p = 0.09 in women). The proportion of frequent (3 times or more) marijuana users was higher for the lower educated than for the higher educated (62.5% vs. 32.1%, p < 0.001 in men and 33.9% vs. 24.4%, p = 0.12 in women). Conclusions Sex, age, ethnicity, and education were significant determinants of alcohol and marijuana use.